2016
DOI: 10.1186/s12966-016-0441-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of organisational-level strategies with or without an activity tracker to reduce office workers’ sitting time: a cluster-randomised trial

Abstract: BackgroundOffice workers engage in high levels of sitting time. Effective, context-specific, and scalable strategies are needed to support widespread sitting reduction. This study aimed to evaluate organisational-support strategies alone or in combination with an activity tracker to reduce sitting in office workers.MethodsFrom one organisation, 153 desk-based office workers were cluster-randomised (by team) to organisational support only (e.g., manager support, emails; ‘Group ORG’, 9 teams, 87 participants), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
189
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(195 citation statements)
references
References 51 publications
6
189
0
Order By: Relevance
“…This effect adds to the challenge of implementing such interventions among people who are not participating in a research project. Brakenridge et al [19] concluded that when the intervention is implemented from within the organization, such as being delivered by the head of the workplace wellness office, it is implemented in a way that suits the organization in question. Choosing this approach to implementation can make these interventions more easily scalable to other workplaces [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect adds to the challenge of implementing such interventions among people who are not participating in a research project. Brakenridge et al [19] concluded that when the intervention is implemented from within the organization, such as being delivered by the head of the workplace wellness office, it is implemented in a way that suits the organization in question. Choosing this approach to implementation can make these interventions more easily scalable to other workplaces [19].…”
Section: Discussionmentioning
confidence: 99%
“…Brakenridge et al [19] concluded that when the intervention is implemented from within the organization, such as being delivered by the head of the workplace wellness office, it is implemented in a way that suits the organization in question. Choosing this approach to implementation can make these interventions more easily scalable to other workplaces [19]. In our case, the researchers came from outside the organizations, performing the intervention with the installment of the treadmill workstations.…”
Section: Discussionmentioning
confidence: 99%
“…It has become a common sense that prolonged sedentary behavior is very unhealthy. This correlates with many preventable diseases and deaths, such as cardiovascular diseases, diabetes, obesity, high blood pressure, colon cancer, and so on (Brakenridge et al, 2016;Dustan et al, 2011;Knaeps et al, 2016; Thorp et al 2011). Sedentary behavior (SB) refers to any waking behavior characterized by an energy expenditure less than or equal to 1.5 METs (or metabolic equivalent) with a sitting or reclining posture during tasks such as working at a desk and watching TV (SBRN, 2012).…”
Section: Prevalence Of Sedentary Behaviors and Associated Health Consmentioning
confidence: 99%
“…A key limitation of the previous trials evaluating the Stand Up Australia intervention is the limited diversity of workplaces (typically, white-collar employees of reasonably large metropolitan organisations have been represented) [7][8][9]. Accordingly, the evaluation used purposive sampling to ensure coverage of desk-based workers in a range of industries (including white-/blue-collar), organisational size (small/medium/large, i.e., <20/20-500/>500), and locations (metropolitan/regional).…”
Section: Study Design and Recruitmentmentioning
confidence: 99%
“…The relevance of addressing workplace sitting time for workplace health and safety [2,3] and for public health [4] has been acknowledged and there have been several recent interventions, incorporating a range of activity-promoting strategies, that have demonstrated that reducing prolonged sitting is feasible and acceptable to both employers and employees within the desk-based workplace [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%